Speed strength. A comprehensive guide to the biomechanics and training methodology of linear speed - Smith, J. (JUST FLY SPORTS, 2019)
In training speed, the most elusive athletic quality, what really works, and what doesn't? What are the components of sprinting itself that elites do, where amateurs falter? And how can we arrange all of this in a training medium that facilitates high performance? Speed Strength is the product of hundreds of athletes trained, thousands of hours of study, dozens of expert mentors, and an open mind. If you are interested in the answer to these questions, then Speed Strength is the book that holds the answers you are looking for, and much more.Joel Smith is the host of the Just Fly Performance Podcast and a track and strength coach of 13 years. As a track coach to national champions and Olympic champions as a strength coach, Joel has seen the elements of speed inside and out. Featuring the insight of over 25 field leaders, Speed Strength touches on the most important trainable elements of sprinting in a holistic and thorough manner.